Persepsi Masyarakat Terhadap Home Schooling: Studi tentang Penyelenggaraan Pendidikan Alternatif (Home Schooling) di Kabupaten Jember: Community Perceptions of Home Schooling: A Study on the Implementation of Alternative Education (Home Schooling) in Jember Regency - St. Rodliyah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2010)
Nowadays, education development in Indonesia is enriched with the trend of home schooling. This familiar and efficient education method has been widely discussed by mass media, even though it has actually emerged for a long time. What do you think of home schooling? In home schooling, it does not mean that Indonesian children become lazy students or just relax at home. In line with the development of knowledge, especially in education, there are some learning methods which can be applied efficiently and even practically, one of which is home schooling. Nevertheless, can home schooling also give positive influence to the children’s mental? The people who run for home schooling system usually have their own community, in which they can socialize with each other. Even so, the term home schooling does not always mean that the children have to study at home. Perkembangan pendidikan di Indonesia saat ini diperkaya dengan tren home schooling. Metode pendidikan yang familiar dan efisien ini telah dibahas secara luas oleh media massa, meskipun sebenarnya telah muncul sejak lama. Bagaimana pandangan Anda tentang home schooling? Dalam home schooling, tidak berarti anak-anak Indonesia menjadi siswa yang malas atau hanya bersantai di rumah. Sejalan dengan perkembangan ilmu pengetahuan, terutama dalam pendidikan, terdapat beberapa metode pembelajaran yang dapat diterapkan secara efisien dan praktis, salah satunya adalah home schooling. Namun, apakah home schooling juga dapat memberikan pengaruh positif terhadap mental anak? Orang-orang yang menerapkan sistem home schooling biasanya memiliki komunitas sendiri, di mana mereka dapat bersosialisasi. Namun, istilah home schooling tidak selalu berarti anak harus belajar di rumah.